ANALISIS YURIDIS ATAS PENGHENTIAN PENYELIDIKAN TINDAK PIDANA PEMALSUAN AKTA AUTENTIK DI DITRESKRIMUM POLDA KALBAR PADA TAHUN 2025 (Studi Kasus Laporan Polisi Nomor: LP/B/178/VI/2024/SPKT/Polda Kalimantan Barat) - NIM. A1012221015, RONI RAMADAN (Fakultas Hukum Universitas Tanjungpura, 2025)
ABSTRACT Following a report from Wahyu Hartoko, the plaintiff and heir of Sukartadji, to the Directorate of General Criminal Investigation (Ditreskrimum) of the West Kalimantan Regional Police, Police Report Number: LP/B/379/XII/2024/SPKT/Polda Kalbar, regarding the forgery of an authentic deed, police officers from the Directorate of General Criminal Investigation (Ditreskrimum) of the West Kalimantan Regional Police conducted an investigation. However, the investigation was ultimately terminated in 2025 on the grounds that the reported act did not constitute a crime, as stated in the letter of termination of investigation, issued by the Director of General Criminal Investigation of the West Kalimantan Regional Police, Letter Number: B/37/I/2025/Ditreskrimum, dated January 20, 2025, concerning Notification of Termination of Investigation. However, there is clear evidence supporting that when Notary/PPAT Evan Dari Rachman, S.H., M.Kn., issued the share sale and purchase deed No. 06 dated August 4, 2023, it was not based on the facts as seen, witnessed, and experienced in a legal act. The problem formulation in this study is: